2011
DOI: 10.1111/j.1445-5994.2011.02443.x
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplasia in the Wellington region 2002–2007: disease incidence and treatment patterns

Abstract: The incidence of myelodysplasia in Wellington, NZ is similar to incidence figures from previously published studies. The treatment these patients received was predominantly supportive through RBC transfusion. Effective iron chelation therapy measures were not used although there appeared to be a low incidence of clinical iron overload in the study population. The data in this study will be available for comparison with future studies to assess trends in incidence, treatment and outcome in myelodysplastic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In a recent MDS cohort without such restriction, only 3 of 70 patients were younger than 40 years [15]. The overall incidence of MDS in the United States per 100,000 individuals aged 70–79 is 20.94 and in those less than 40 years only 0.14 [16].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent MDS cohort without such restriction, only 3 of 70 patients were younger than 40 years [15]. The overall incidence of MDS in the United States per 100,000 individuals aged 70–79 is 20.94 and in those less than 40 years only 0.14 [16].…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of MDS, which still remains inaccurate, has been reported to vary-3.2/10 5 [1] and 7.7/10 5 [2] in France, 6/10 5 [3] and 12.6/10 5 [4] in the UK, 3.3/10 5 in the USA [5], 1.24/ 10 5 in European cancer registries [6], 2.75/10 5 in New Zealand [7], and 1.0/10 5 in Japan [8]. The reported incidence differs greatly among countries (Table 1).…”
mentioning
confidence: 99%
“…Hiwase et al 18 "RBC transfusion dependent patients had inferior overall survival compared to RBC transfusion independent patients" "RBC transfusion dependence was an independent adverse prognostic markers" Irwin et al 19 "Despite the observed increase in serum ferritin over the course of this study, and despite not receiving iron chelation therapy, the majority of transfusion dependent MDS patients did not develop a clinical syndrome of iron overload." Kim et al 21 "patients with MDS (…) requiring chronic transfusions have higher RBC alloimmunization rates than other transfused patient populations."…”
Section: Survivalmentioning
confidence: 82%
“…Nine studies reported outcomes relating to iron overload and its complications. 10,12,19,24,27,30,32,37,43 Three studies found an increased risk of iron overload complications among transfused MDS patients, including presentations of cardiomyopathy/heart failure, conduction disorders, diabetes and liver disease. 10,27,30 Two studies examined magnetic resonance imaging evidence of iron deposition with conflicting results about the correlation between liver iron and transfusion burden.…”
Section: Clinical Complicationsmentioning
confidence: 99%